(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The process of making most manganese steels involves raising the melting and casting temperatures to 1500 oC and above to increase the fluidity of the metal and facilitate slag removal. It helps to separate alloy elements with micro and macro carbide at high temperature and to form brittle transformation products. The presence of segregation at the grain boundaries serves as an obstacle for the movement of dislocations. This can result in uneven, inconsistent corrosion rates of the steel and the quality of the alloy. This article investigates the effect of casting/melting temperature on the carbide segregation tendency of austenitic microstructure manganese steel and its effect on the corrosion resistance properties of jaw crushers.